(untitled) (Global Scientific Review, 2023)
the article highlights the rapid development of the Uzbek energy sector in the context of globalization, revolutionary changes in the technologies of its creation, storage and distribution, the use of alternative energy sources – wind and solar power plants, the problems of renewable energy sources and changes in energy consumption, despite all their advantages.